Evaluación de procesos oxidativos avanzados homogéneos para el tratamiento de efluentes del camal municipal de la ciudad de Calceta - Martínez Cedeño, Jeniffer Estefanía (2024)
The objective of this study was to evaluate homogeneous advanced oxidative processes for the treatment of effluents from the Calceta municipal slaughterhouse. The research was carried out in three phases: wastewater characterization, application of advanced oxidative processes and determination of toxicity. In the first phase, the physicochemical characteristics of the effluent were determined, including parameters such as color, conductivity, pH and turbidity. In the second phase, photocatalysis (UV/H₂O₂O₂) and Photo-Fenton methods were used to treat the wastewater, evaluating their efficiency in reducing pollutants. In the third phase, the toxicity of the effluent before and after the treatments was quantified using bioassays with Daucus carota seeds. The methods used included statistical analysis, deductive and bibliographic methods, sampling techniques, georeferencing and observation. The processes were implemented in a bench reactor, and the data were analyzed by analysis of variance. Photocatalysis and Photo-Fenton achieved significant decreases in color, conductivity, pH and turbidity parameters accepting the alternative hypothesis of the research. In addition, toxicity tests showed that Daucus carota species experienced a reduction in their germination rate reaching only 1.37% in the applied treatment, but as the concentration of the treatment solution was diluted, their behavior is similar to the negative control.